2016
DOI: 10.3233/jad-151006
|View full text |Cite
|
Sign up to set email alerts
|

Regular Benzodiazepine and Z-Substance Use and Risk of Dementia: An Analysis of German Claims Data

Abstract: The restricted use of BDZRs may contribute to dementia prevention in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 26 publications
7
33
2
3
Order By: Relevance
“…In most of the studies, the time lag in main analyses has been 1–2 years , and in one study 5 years . These studies have been inconsistent, with some claiming that BZDRs and BZDs are AD/dementia risk factors and others reporting no association . One, without any time lag reported that BZDs were associated with decreased risk of AD .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the studies, the time lag in main analyses has been 1–2 years , and in one study 5 years . These studies have been inconsistent, with some claiming that BZDRs and BZDs are AD/dementia risk factors and others reporting no association . One, without any time lag reported that BZDs were associated with decreased risk of AD .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on dose–response relationship of BZDs have been equally heterogeneous, with two studies showing a dose–response effect , one reporting an increased risk with smaller cumulative doses only , and one reporting null results . We are aware on only one study that assessed association between Z drugs and AD or vascular dementia, concluding with null results .…”
Section: Introductionmentioning
confidence: 99%
“…All other studies focused on the association between BZD and dementia risk. Eight case control studies (Billioti de Gage et al, ; Chan et al, ; Gomm et al, ; Imfeld, Bodmer, Jick, & Meier, ; Takada, Fujimoto, & Hosomi, ; Tapiainen et al, ; C.‐S. Wu, Ting, Wang, Chang, & Lin, ; C.‐S.…”
Section: Resultsmentioning
confidence: 99%
“…The AOK covers about 50% of the German population at least 80 years old and one third of the total population at least 50 years old [20]. The AOK data set includes the ambulatory as well as the hospital sector of the health care system.…”
Section: Methodsmentioning
confidence: 99%
“…The covariates were selected based on existing evidence and previous publications on the topic of dementia risk and gout diagnoses [18, 2022]. We considered comorbidity as present if it was reported in at least one quarter during the observation time, and in at least two quarters during the study time.…”
Section: Methodsmentioning
confidence: 99%